Botanical studies, antimicrobial activity and cytotoxity of Eleutherine bulbosa (Mill.) Urb (Research, Society and Development, 2020)
The use bulbs of Eleutherine bulbosa for treatament of diseases caused by malaria, amoeba and bacteria. This study accomplished the botanical and phytochemical characterization, antimicrobial activity and cytotoxic of E. bulbosa. For the anatomical studies, the studied material was fixed in formaldehyde – acetic acid and ethanol and it was dyed in safranin and in astra blue. For histochemistry, was fixed in buffered neutral formalin and in ferrous sulphate in formalina. Ethanolic Extract (EE) was submitted to fractionation in a chromatographic column and four (4) fractions were obtained from it. The Dichloromethane Fraction (DF) was submitted to a new fractionation. The biological activity was evalueted by diffusion in agar, microdilution and celular viability MTT. The bulb of E. bulbosa is characterized by a reduced caulinar axis and by succulent amiliferous cataphylls, epidermis with the presence of anthocyanins, homogeneous mesophyll with idioblasts of prismatic crystals of calcium oxalate and phenolic compounds. In agar diffusion it was observed that EE, DF and ethyl acetate fraction (ACF) were active for Staphylococcus aureus. In microdilution, DF (Inhibitory minimum concentration= 125 µg/ mL) was more active. For all samples the Minimous Bactericidal Concentration was >1000 µg/ mL. The fractionation contributes positively with the citotoxicity, being subfractions S1 and S2 the most citotoxic ones. The Fraction Dichloromethane was the most active one for S. aureus and more citotoxicity to VERO cells. Probably the less citotoxicity of EE is related to the presence of anthocyanins that are present on bulbs epidermis.